Exploring Integration in Education through Blockchain Technology - Awerika, Charlotte Katherine; Alian Amerila, Zara Mazelene; Ameria, Sharddha; Ameriya, Tanisha; Atsumi, Masakazu (IAIC Bangun Bangsa, 2023)
New technological advances and the availability of high-speed connections have brought about significant changes in our daily lives. However, behind all these conveniences, we are also faced with complex security challenges. One of the innovations that has really attracted attention is Blockchain technology, which has become the most influential invention in the last decade. Blockchain promises extraordinary security in supply chain management, including in the shipping industry and other fields. In addition, the education sector also sees tremendous potential in utilizing this technology. Universities and other educational institutions are working on using blockchain technology to enhance teaching and learning processes and strengthen collaboration between students, teachers and parents. Blockchain applications are also expected to be used in the creation of electronic transcripts, digital certification, cloud storage and identity management. Ongoing studies have revealed the maximum potential of blockchain technology in education and how it can be utilized effectively.